Source of Genetic Aberrations in Human Embryonic Stem Cell : Common Fragile Sites and Replication Stress - Ivanna Williantarra (Cermin Dunia Kedokteran, 2017)
The capability of human embryonic stem cell (hESC) to form all cell types of the human body has made them highly attractive for therapeutic applications. Amongst others, the usefulness of hESC in therapeutic applications highly relies on their genomic integrity and stability. However, hESCs are well documented to frequently acquire genetic changes such as aneuploidies, segmental deletions or amplifications, epigenetic changes, and mitochondrial DNA mutations. This leads to safety concerns regarding the use of hESC in cell-based therapies. Certain genetic or epigenetic changes in hESC might lead not only to altered differentiation potential, but also increased proliferation capacity. A major concern is that, in vivo, this change might lead to tumorigenesis. These review will highlight the reported genetic aberrations found in human embryonic stem cell as a result of replication stress caused by naturally occurring common fragile sites in hESC.Kemampuan sel punca embrionik manusia untuk berdiferensiasi membentuk seluruh lini sel tubuh manusia telah membuka peluang penggunaan sel punca untuk aplikasi terapetik. Penggunaan sel punca embrionik untuk aplikasi terapetik sangat bergantung pada stabilitas dan integritas genomiknya. Sayangnya, sel punca embrionik sering ditemukan memiliki perubahan-perubahan genetik seperti aneuploidi, duplikasi dan amplifikasi segmental, perubahan epigenetic dan mutasi DNA mitokondria. Hal ini menyebabkan munculnya isu keamanan penggunaan sel punca untuk terapi sel. Beberapa perubahan genetik ataupun epigenetik pada sel punca tidak hanya mengubah potensi diferensiasi namun juga kapasitas proliferasi sel sehingga menimbulkan kekuatiran transformasi sel menjadi sel kanker in vivo. Ulasan ini akan membahas kelainan-kelainan genetik yang ditemukan pada sel punca embrionik manusia yang disebabkan oleh stres replikasi oleh adanya situs rapuh umum. Ivanna Williantarra.